STRATEGI GURU TAMAN KANAK-KANAK BERNUANSA HINDU DALAM MENGEMBANGKAN NILAI PENDIDIKAN KARAKTER - Mahendriani, Ni Made Ayu; Sumertha, I Wayan; Purwanto, Susilo Edi (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2022)
Education is an important factor that has a major influence on the process and learning outcomes of a student. Likewise with development in character education which also demands activities as well as the creativity and character of a teacher in shaping personal competence in students. How is the strategy of Kindergarten Teachers with Hindu nuances in planning the development of character education values and the development of character education values. This study uses a qualitative research type by applying the case method. The results of the study show that the teacher prepares daily learning plans, semester programs and includes annual programs, the use of learning media, educators must pay attention to models, methods and strategies and understand the character of students' children and through integrated classroom teaching and learning activities in each subject, extracurricular activities, as well as daily activities at home and in the community.